PENERAPAN STRATEGI DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Stephanie Claudy Manurung; M. H Sumampow; Christny F. E Rompas (SOSCIED, 2023)
One of the teacher's tasks is to develop learning methods. An example of a method that can be used is discovery learning. The aim of this research is to discuss improving student learning outcomes on virus material through the application of the Discovery Learning strategy. Due to this, this study will use this learning strategy to improve student learning outcomes on viral material. This study focuses on finding out the application of the Discovery Learning Strategy in improving learning outcomes for class X students at SMAN 1 Maesaan for the 2022/2023 academic year. The researcher used the PTK research strategy with the research subjects being 24 class X MIA 1 students. This study uses observation sheets to collect data. The results of the research show that there is an increase in student learning outcomes for viral material. This is proven by the average score in the first cycle posttest of 70.16. The average value that increased in the second cycle posttest was 77.3%. Therefore, we can conclude that Discovery Learning is able to improve the learning outcomes of class X MIA 1 SMAN 1 Maesaan students.